Technological Information Management in Operational Processes for a Transportation Sector Company - BRAVO HUIVIN, ELIZABETH KRISTINA; Blas-Zavaleta, Jessica Nicoll; Cano-Zurita, Fatima (LACCEI, 2025)
Information Technology Management as a Proposal for Implementation in the Operational Processes in the Transportation Sector in Trujillo, Peru. This study is framed within a research approach that utilizes quantitative and qualitative data collection methods, such as surveys, observation sheets, and interviews. The proposal focuses on developing a website aimed at modernizing and optimizing the key processes: ticket sales, parcel management, and customer service. The main objective is to improve operational efficiency, enhance the customer experience, reduce processing times and errors, and strengthen the company’s competitiveness in the market. The results demonstrate that the implementation of Information Technology Management contributed significantly to productivity, recording an increase of 67.10%. Moreover, user satisfaction increased by 28.9% following the incorporation of the website, with the implementation of an information system being rated as highly profitable, highlighting that it could automate up to 80% of the operational processes. Additionally, a post-implementation revenue comparison was calculated, obtaining a margin of +27.78%, which confirms the project’s long-term profitability. The article covers the following sections: introduction, state of the art, objectives, materials and methods, methodology, results, discussion, and conclusions.